Ghana Airport Company Limitedas Decoupling Experience: Achievements, Challenges and Policy Lessons (Global Journal of Management and Business Research, 2013)
Employee Commitment â€“ Investor in People Model Kazi Afaq Ahmed General Manager Administration and Legal Green Star Social Marketing, Pakistan & Prof. (Meritorious) Dr. Abuzar Wajidi Dean, Faculty of Management and Administrative Sciences University of Karachi Abstract: The performance of the organization is directly impacted by level of Employees Commitmentâ€. The â€œEmployee Commitmentâ€ â€“Investors in People (IIP) Model was selected as the reference sample for this study. The IIP model emerged in UK and is being successfully implemented in the western countries. Lot of prior research has been carried out across the world on IIP however no research work is done to test the validity of this model in developing countries like Pakistan. As per IIP, the employee commitment is dependent variable of four independent variables i.e employee contribution recognition, support people development, equality of opportunities and encourages performance improvement. This study was based on the hypothesis thatâ€ IIP said employee commitment variables are secondary and tertiary motivators and are not workable in Pakistan unless primary needs of the employees are fulfilledâ€. The research study conducted in group of sample organizations comprising of multinational and local private organizations has confirmed the above hypothesis. The research findings concludes that â€œFair and Equitable Compensation & Benefitsâ€, Decent Work Environment, and People Development are key elements for firing up Employee Commitmentâ€, in developing countries like Pakistan. The research findings and recommendations will help local entrepreneurs to improve productivity; quality of output and retaining highly motivated and charged workforce committed to improve organizational performance. Key words: Employee Commitment, Investors in People (IIP), Compensation & Benefit, Decent Work Environment, People Development, Organizational Performance Introduction Problem statement: The emerging cha
Keywords: aims; achievements; effects; challenges and implications